Perovskite solar cell and preparation method and application thereof
By using (FA0.95MA0.05)0.95Cs0.05Pb(I0.95Br0.05)3 and dimethylphenethyl thiodine as perovskite absorber layer materials in perovskite solar cells, the inefficiency problem caused by the defect of the perovskite absorber layer is solved, and a more efficient, stable and durable perovskite solar cell is achieved.
Patent Information
- Application Number
- CN202411993156.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the perovskite absorber layer of perovskite solar cells has defects, resulting in low cell efficiency.
Perovskite absorbing layer materials including (FA0.95MA0.05)0.95Cs0.05Pb(I0.95Br0.05)3 and dimethylphenethyl thiodine were used, and the crystallization quality and defect density were optimized by specific laminated structures and treatment methods.
The crystallization quality of the perovskite absorber layer is significantly optimized, defects are reduced, and light absorption and charge transfer efficiency is improved, thereby improving the overall performance of the battery, including efficiency, stability and durability.
Smart Images

Figure CN119768015A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, and in particular to a perovskite solar cell and a preparation method and application thereof. Background Art
[0002] Perovskite is a class of materials with a unique crystal structure. Perovskite has gradually expanded from the initial mineralogy research to multiple fields such as physics, chemistry, materials science and even energy technology. Its unique chemical composition CaTiO3 not only gives it a specific crystal structure, but also lays a solid foundation for its application in multiple fields. In materials science, the perovskite structure has been widely studied for the preparation of various functional materials due to its high symmetry and adjustable electronic structure characteristics. Especially in the field of energy conversion and storage, perovskite materials have shown great potential. Among them, the most representative application is perovskite solar cells.
[0003] Perovskite solar cells use perovskite materials as light absorption layers to convert solar energy into electrical energy through the photoelectric effect. The core lies in the photoelectric conversion efficiency of perovskite materials, that is, the absorbed photons can be efficiently converted into electrons and holes to generate current. The quality of perovskite films has a crucial impact on cell efficiency. However, in the current production process, the perovskite light absorption layer often has defects to varying degrees, which affects the efficiency of perovskite solar cells. How to reduce the defects of the perovskite light absorption layer in the production process and achieve the optimal crystal growth of the film still requires further research and exploration. Summary of the invention
[0004] The present invention aims to solve the problem of low efficiency of perovskite solar cells caused by defects in the perovskite light absorption layer of the perovskite solar cells prepared in the prior art. The present invention provides a perovskite solar cell and a preparation method and application thereof.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a perovskite solar cell, comprising a conductive substrate, a hole transport layer, a self-assembled monolayer, a perovskite light absorption layer, a passivation layer, an electron transport layer and a top electrode layer which are stacked in sequence; The material of the perovskite light absorbing layer includes (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 and dimethylphenylethylthiodide.
[0006] The molar fraction of the dimethylphenylethylmercapto iodide is 1% to 5%.
[0007] The material of the hole transport layer is NiO x , x is one of 1~1.5, CuSCN or CuI.
[0008] The material of the self-assembled monolayer is one or more of MeO-2PACz, 2PACz, Me-4PACz or 4PACz.
[0009] The material of the passivation layer is one or more of PEAI, PEACl, mF-PEAI or BAI.
[0010] The material of the electron transport layer includes TiO2, SnO2 or one of fullerene and fullerene derivatives.
[0011] The material of the conductive substrate is indium tin oxide, and the material of the top electrode layer is one of gold, silver, copper, graphite or amorphous carbon.
[0012] The thickness of the conductive substrate is 200~400nm; the thickness of the hole transport layer is 20~40nm; the thickness of the self-assembled monolayer is 1~5nm; the thickness of the perovskite light absorption layer is 300~700nm; the thickness of the passivation layer is 1~5nm; the thickness of the electron transport layer is 10~100nm; and the thickness of the top electrode layer is 50~500nm.
[0013] The present invention also provides a method for preparing a perovskite solar cell, comprising: A hole transport layer is obtained by magnetron sputtering a hole transport layer material on a conductive substrate and annealing the material; Spin coating a solution including a self-assembled monomolecular material on the hole transport layer, and annealing after spin coating to form a self-assembled monomolecular layer; Spin coating on self-assembled monolayers includes (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 and dimethylphenylethylthiodithiodide perovskite precursor solution, performing two-stage spin coating at different rotation speeds, adding chlorobenzene to the perovskite precursor solution before the end of spin coating, and annealing after spin coating to obtain a perovskite light absorbing layer; Spin coating a solution including a passivation material on the perovskite light absorbing layer, and annealing after spin coating to form a passivation layer; An electron transport material and a top electrode material are sequentially deposited on the passivation layer by vacuum evaporation to form an electron transport layer and a top electrode layer, respectively, to constitute a perovskite solar cell.
[0014] The present invention also provides a photovoltaic device, comprising the above-mentioned perovskite solar cell.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The perovskite light absorbing layer material of the perovskite solar cell provided by the present invention comprises (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 and dimethylphenylethylmercapto iodine can optimize the crystal quality, reduce defects, improve light absorption and charge transfer efficiency, and thus improve the overall performance of the battery. The unique molecular structure of adding dimethylphenylethylmercapto iodine can guide the orderly and uniform growth of perovskite crystals, while effectively filling or passivating defects in the film, reducing defect density and reducing carrier recombination losses; in addition, the strong coordination ability of the mercapto group in dimethylphenylethylmercapto iodine forms a stable chemical bond with the metal ions in the perovskite material, significantly enhancing the environmental stability of the film; the perovskite solar cell provided by the present invention can comprehensively improve the efficiency, stability and durability of the perovskite solar cell.
[0016] Furthermore, the material of the hole transport layer is NiO x , CuSCN or CuI, these materials have good hole transport properties, which can effectively promote the transmission of photogenerated holes from the perovskite light-absorbing layer to the electrode, reduce hole accumulation, and improve the open circuit voltage and fill factor of the battery.
[0017] Furthermore, one or more of MeO-2PACz, 2PACz, Me-4PACz or 4PACz are used to form a self-assembled monolayer, which can serve as an interface modification layer to improve the contact between the perovskite light absorbing layer and the hole transport layer, reduce interface recombination, and improve charge transfer efficiency.
[0018] Furthermore, using one or more of PEAI, PEACl, mF-PEAI or BAI to form a passivation layer can effectively passivate the surface defects of the perovskite light-absorbing layer, reduce non-radiative recombination, improve the stability of the battery, and may also improve charge extraction and transmission.
[0019] Furthermore, an electron transport layer formed by TiO2, SnO2 or fullerene and a fullerene derivative has good electron transport performance and can quickly transfer photogenerated electrons from the perovskite light-absorbing layer to the electrode, thereby reducing electron accumulation and increasing the short-circuit current density of the battery.
[0020] Furthermore, the conductive glass is made of indium tin oxide, which has good light transmittance and conductivity and is suitable as a substrate for solar cells. The selection of the top electrode layer material ensures good electrical contact and charge collection efficiency.
[0021] As an additive, dimethylphenylethylthiodide can significantly optimize the crystallization quality of the perovskite light-absorbing layer, reduce defects, improve light absorption and charge transfer efficiency, and thus improve the photoelectric conversion efficiency of the battery.
[0022] The photovoltaic device provided by the present invention has efficient and stable photoelectric conversion capabilities due to the use of the above-mentioned high-performance perovskite solar cell, and is suitable for photovoltaic power stations, rooftop photovoltaic systems, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following is a brief introduction to the drawings required for use in the present invention: Figure 1 is a schematic diagram of a perovskite solar cell of the present invention; In the figure, 1. conductive substrate; 2. hole transport layer; 3. self-assembled monolayer; 4. perovskite light absorption layer; 5. passivation layer; 6. electron transport layer; 7. top electrode layer. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with the accompanying drawings: In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] like Figure 1 As shown, a perovskite solar cell provided by the present invention includes a conductive substrate 1, a hole transport layer 2, a self-assembled monolayer 3, a perovskite light absorption layer 4, a passivation layer 5, an electron transport layer 6 and a top electrode layer 7 which are stacked in sequence.
[0026] The material of the hole transport layer is nickel oxide (NiO x (x is 1-1.5)), cuprous thiocyanate (CuSCN) or cuprous iodide (CuI). Preferably, the hole transport layer is made of NiO x (x value is 1~1.5).
[0027] The material of the self-assembled monolayer is one or more of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz), (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid (Me-4PACz) or [4-(9H-carbazole-9-yl)butyl]phosphonic acid (4PACz). Preferably, the material of the self-assembled monolayer is MeO-2PACz.
[0028] The material of the perovskite light absorbing layer includes (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 ) 3 and an additive, wherein the additive is dimethylphenylethylmercapto iodide, and the molar fraction of dimethylphenylethylmercapto iodide is 1% to 5%. Preferably, the molar fraction of the dimethylphenylethylmercapto iodide is 2% to 3%.
[0029] The material of the passivation layer is one or more of phenylethylamine iodide (PEAI), phenylethylamine chloride (PEACl), m-fluorophenylethylamine iodide (mF-PEAI) or butylamine iodide (BAI), more preferably mF-PEAI. The material of the electron transport layer is titanium dioxide (TiO2), tin oxide (SnO2) or fullerene (C 60 ) and a fullerene derivative. Preferably, the material of the electron transport layer is C 60 .
[0030] The material of the top electrode layer is one of gold, silver, copper, graphite or amorphous carbon. Preferably, the material of the top electrode layer is gold.
[0031] The conductive substrate is transparent conductive glass, and the transparent conductive glass is indium tin oxide (FTO).
[0032] In an embodiment of the present invention, the thickness of the conductive substrate is 200-400nm, preferably 250-350nm; specifically 290nm, 300nm, 310nm, 320nm, etc. The thickness of the hole transport layer is 20-40nm, preferably 25-35nm; specifically 26nm, 27nm, 28nm, 29nm, 30nm, 31nm, 32nm, 33nm, 34nm or 35nm. The thickness of the self-assembled monolayer is 1-5nm, preferably 1-3nm, and more preferably 1-2nm. The thickness of the perovskite light absorption layer is 300-700nm, preferably 300-500nm, and more preferably 400-500nm. The thickness of the passivation layer is 1-5nm, preferably 1-3nm, and more preferably 1-2nm. The thickness of the electron transport layer is 10-100nm, preferably 20-80nm, more preferably 30-60nm, and most preferably 40-50nm. The thickness of the top electrode is 50-500 nm, preferably 100-400 nm, and more preferably 100-200 nm.
[0033] In the following examples, unless otherwise specified, all materials used can be obtained through common channels; and the test methods adopted are conventional methods in the art.
[0034] Embodiment 1: The method for preparing the perovskite solar cell of this embodiment includes: S1, wash the FTO glass substrate with acetone, isopropanol and deionized water in sequence, blow dry and set aside; S2, NiO was deposited on FTO glass substrate by magnetron sputtering x (x is 1~1.5), and then annealed in an environment of 300℃ for 10 minutes to form a hole transport layer with a thickness of about 30 nm; S3, spin coating MeO-2PACz solution (solvent is isopropanol, MeO-2PACz solution concentration is 0.3 mg / mL) on the hole transport layer at a rotation speed of 3000 rpm for 30 seconds, and then annealing in an environment of 100°C for 10 minutes to form a self-assembled monolayer, the thickness of the self-assembled monolayer is about 2 nm; S4, prepared according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05)3 Perovskite precursor solution (concentration of 1.5 mol / L, solvent DMF:DMSO=4:1, wherein the molar fraction of dimethylphenylethylthiodide is 2%), 100 μL of the perovskite precursor solution is spin-coated on the self-assembled monolayer, the first stage of spin coating is 2000 rpm, the spin coating is 10 s, the second stage of spin coating is 5000 rpm, the spin coating is 40 s, 15 s before the end of spin coating, 200 μL of chlorobenzene is quickly added as an anti-solvent, and then annealed on a hot stage at 100°C for 30 minutes to form a perovskite light absorbing layer, the thickness of the perovskite light absorbing layer is about 400 nm; S5, spin coating the mF-PEAI passivation solution (mF-PEAI concentration is 0.5 mg / mL) on the perovskite light absorbing layer at a rotation speed of 3000 rpm for 30 seconds, and then annealing on a hot stage at 100°C for 10 minutes to form a passivation layer with a thickness of about 2 nm; S6, depositing C on the passivation layer by vacuum evaporation 60 , forming an electron transport layer, the thickness of the electron transport layer is about 40nm; S7, depositing gold on the electron transport layer by vacuum evaporation to form a top electrode layer, the thickness of the top electrode layer is about 100 nm; the perovskite solar cell of this embodiment is manufactured through the above steps.
[0035] Embodiment 2: The method for preparing the perovskite solar cell of this embodiment includes: S1, wash the FTO glass substrate with acetone, isopropanol and deionized water in sequence, blow dry and set aside; S2, NiO was deposited on FTO glass substrate by magnetron sputtering x (x is 1~1.5), and then annealed in an environment of 300℃ for 10 minutes to form a hole transport layer with a thickness of about 30 nm; S3, spin coating Me-4PACz solution (solvent is isopropanol, Me-4PACz solution concentration is 0.3 mg / mL) on the hole transport layer at a speed of 3000 rpm for 30 seconds, and then annealing in an environment of 100°C for 10 minutes to form a self-assembled monolayer, the thickness of the self-assembled monolayer is about 3 nm; S4, prepared according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05)3 Perovskite precursor solution (concentration of 1.5 mol / L, solvent DMF:DMSO=4:1, wherein the molar fraction of dimethylphenylethylthiodide is 3%), 100 μL of the perovskite precursor solution is spin-coated on the self-assembled monolayer, the first stage of spin coating is 2000 rpm, the spin coating is 10 s, the second stage of spin coating is 5000 rpm, the spin coating is 40 s, 200 μL of chlorobenzene is quickly added as an anti-solvent 15 s before the end of spin coating, and then annealed on a hot stage at 100°C for 30 minutes to form a perovskite light absorbing layer, the thickness of the perovskite light absorbing layer is about 400 nm; S5, spin coating PEAI passivation solution (PEAI concentration is 0.5 mg / mL) on the perovskite light absorbing layer at a rotation speed of 3000 rpm for 30 seconds, and then annealing on a hot stage at 100 °C for 10 minutes to form a passivation layer with a thickness of about 2 nm; S6, depositing SnO2 on the passivation layer by vacuum evaporation to form an electron transport layer, the thickness of the electron transport layer is about 50 nm; S7, depositing graphite on the electron transport layer by vacuum evaporation to form a top electrode layer, the thickness of the top electrode layer is about 200 nm; the perovskite solar cell of this embodiment is manufactured through the above steps.
[0036] Embodiment 3: The method for preparing the perovskite solar cell of this embodiment includes: S1, wash the FTO glass substrate with acetone, isopropanol and deionized water in sequence, blow dry and set aside; S2, CuSCN was magnetron sputtered on the FTO glass substrate, and then annealed at 300 °C for 10 min to form a hole transport layer with a thickness of about 30 nm; S3, spin coating MeO-2PACz solution (solvent is isopropanol, MeO-2PACz solution concentration is 0.3 mg / mL) on the hole transport layer at a rotation speed of 3000 rpm for 30 seconds, and then annealing in an environment of 100°C for 10 minutes to form a self-assembled monolayer, the thickness of the self-assembled monolayer is about 3 nm; S4, prepared according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05)3 Perovskite precursor solution (concentration of 1.5 mol / L, solvent DMF:DMSO=4:1, wherein the molar fraction of dimethylphenylethylthiodide is 1%), 100 μL of the perovskite precursor solution is spin-coated on the self-assembled monolayer, the first stage of spin coating is 2000 rpm, the spin coating is 10 s, the second stage of spin coating is 5000 rpm, the spin coating is 40 s, 15 s before the end of spin coating, 200 μL of chlorobenzene is quickly added as an anti-solvent, and then annealed on a hot stage at 100°C for 30 minutes to form a perovskite light absorbing layer, the thickness of the perovskite light absorbing layer is about 500 nm; S5, spin coating the mF-PEAI passivation solution (mF-PEAI concentration is 0.5 mg / mL) on the perovskite light absorbing layer at a rotation speed of 3000 rpm for 30 seconds, and then annealing on a hot stage at 100°C for 10 minutes to form a passivation layer with a thickness of about 1 nm; S6, depositing TiO2 on the passivation layer by vacuum evaporation to form an electron transport layer, the thickness of the electron transport layer is about 50 nm; S7, depositing gold on the electron transport layer by vacuum evaporation to form a top electrode layer, the thickness of the top electrode layer is about 300 nm; the perovskite solar cell of this embodiment is manufactured through the above steps.
[0037] Embodiment 4: The method for preparing the perovskite solar cell of this embodiment includes: S1, wash the FTO glass substrate with acetone, isopropanol and deionized water in sequence, blow dry and set aside; S2, NiO was deposited on FTO glass substrate by magnetron sputtering x (x is 1~1.5), and then annealed in an environment of 300℃ for 10 minutes to form a hole transport layer with a thickness of about 30 nm; S3, spin coating MeO-2PACz solution (solvent is isopropanol, MeO-2PACz solution concentration is 0.3 mg / mL) on the hole transport layer at a rotation speed of 3000 rpm for 30 seconds, and then annealing in an environment of 100°C for 10 minutes to form a self-assembled monolayer, the thickness of the self-assembled monolayer is about 3 nm; S4, prepared according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05)3 Perovskite precursor solution (concentration of 1.5 mol / L, solvent DMF:DMSO=4:1, wherein the molar fraction of dimethylphenylethylthiodide is 5%), 100 μL of the perovskite precursor solution is spin-coated on the self-assembled monolayer, the first stage of spin coating is 2000 rpm, the spin coating is 10 s, the second stage of spin coating is 5000 rpm, the spin coating is 40 s, 200 μL of chlorobenzene is quickly added as an anti-solvent 15 s before the end of spin coating, and then annealed on a hot stage at 100°C for 30 minutes to form a perovskite light absorbing layer, the thickness of the perovskite light absorbing layer is about 400 nm; S5, spin coating the mF-PEAI passivation solution (mF-PEAI concentration is 0.5 mg / mL) on the perovskite light absorbing layer at a rotation speed of 3000 rpm for 30 seconds, and then annealing on a hot stage at 100°C for 10 minutes to form a passivation layer with a thickness of about 2 nm; S6, depositing C on the passivation layer by vacuum evaporation 60 ,, forming an electron transport layer, the thickness of the electron transport layer is about 40nm; S7, depositing gold on the electron transport layer by vacuum evaporation to form a top electrode layer, the thickness of the top electrode layer is about 100 nm; the perovskite solar cell of this embodiment is manufactured through the above steps.
[0038] Comparative Example 1: The preparation method of the perovskite solar cell of this comparative example comprises: S1, wash the FTO glass substrate with acetone, isopropanol and deionized water in sequence, blow dry and set aside; S2, NiO was deposited on FTO glass substrate by magnetron sputtering x (x is 1~1.5), and then annealed in an environment of 300℃ for 10 minutes to form a hole transport layer with a thickness of about 30 nm; S3, spin coating MeO-2PACz solution (solvent is isopropanol, MeO-2PACz solution concentration is 0.3 mg / mL) on the hole transport layer at a speed of 3000 rpm for 30 seconds, and then annealing in an environment of 100°C for 10 minutes to form a self-assembled monolayer, the thickness of the self-assembled monolayer is about 3 nm; S4, prepared according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05)3 Perovskite precursor solution (concentration of 1.5 mol / L, solvent DMF:DMSO=4:1, no additives), take 100 μl of perovskite precursor solution and spin coat it on the self-assembled monolayer, the first stage of spin coating has a rotation speed of 2000 rpm, spin coating for 10 s, the second stage of spin coating has a rotation speed of 5000, spin coating for 40 s, 15 s before the end of spin coating, quickly add 200 μl of chlorobenzene as an anti-solvent, and then anneal on a hot stage at 100°C for 30 minutes to form a perovskite light absorbing layer, the thickness of the perovskite light absorbing layer is about 400 nm; S5, spin coating the mF-PEAI passivation solution (mF-PEAI concentration is 0.5 mg / mL) on the perovskite light absorbing layer at a rotation speed of 3000 rpm for 30 seconds, and then annealing on a hot stage at 100°C for 10 minutes to form a passivation layer with a thickness of about 3 nm; S6, depositing C on the passivation layer by vacuum evaporation 60 ,, forming an electron transport layer, the thickness of the electron transport layer is about 40nm; S7, depositing gold on the electron transport layer by vacuum evaporation to form a top electrode layer, the thickness of the top electrode layer is about 100 nm; the perovskite solar cell of this comparative example is manufactured through the above steps.
[0039] Battery performance test: The performance of the perovskite solar cells prepared in the examples and comparative examples was tested under room temperature using a 3A solar simulator at 100 mW / cm 2 The photoelectric conversion efficiency of the cells prepared in the embodiment and the comparative example was tested under the light intensity of 0.084 cm 2 The test results are shown in Table 1: Table 1
[0040] It can be seen from Table 1 that the photoelectric conversion efficiency of Example 1 is increased by 1.6% compared with that of Comparative Example 1, which significantly improves the photoelectric conversion efficiency of the perovskite solar cell.
[0041] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0042] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.
Claims
1. A perovskite solar cell, characterized in that: It includes a conductive substrate, a hole transport layer, a self-assembled monolayer, a perovskite light absorption layer, a passivation layer, an electron transport layer and a top electrode layer which are stacked in sequence; The material of the perovskite light absorbing layer includes (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 and dimethylphenylethylthiodide.
2. A perovskite solar cell according to claim 1, characterized in that: The molar fraction of the dimethylphenylethylmercapto iodide is 1% to 5%.
3. A perovskite solar cell according to claim 1, characterized in that: The material of the hole transport layer is NiO x , x is one of 1~1.5, CuSCN or CuI.
4. A perovskite solar cell according to claim 1, characterized in that: The material of the self-assembled monolayer is one or more of MeO-2PACz, 2PACz, Me-4PACz or 4PACz.
5. A perovskite solar cell according to claim 1, characterized in that: The material of the passivation layer is one or more of PEAI, PEACl, mF-PEAI or BAI.
6. A perovskite solar cell according to claim 1, characterized in that: The material of the electron transport layer includes TiO2, SnO2 or one of fullerene and fullerene derivatives.
7. A perovskite solar cell according to claim 1, characterized in that: The material of the conductive substrate is indium tin oxide, and the material of the top electrode layer is one of gold, silver, copper, graphite or amorphous carbon.
8. A perovskite solar cell according to claim 1, characterized in that: The thickness of the conductive substrate is 200~400nm; the thickness of the hole transport layer is 20~40nm; the thickness of the self-assembled monolayer is 1~5nm; the thickness of the perovskite light absorption layer is 300~700nm; the thickness of the passivation layer is 1~5nm; the thickness of the electron transport layer is 10~100nm; and the thickness of the top electrode layer is 50~500nm.
9. A method for preparing a perovskite solar cell, characterized in that: include: A hole transport layer is obtained by magnetron sputtering a hole transport layer material on a conductive substrate and annealing the material; Spin coating a solution including a self-assembled monomolecular material on the hole transport layer, and annealing after spin coating to form a self-assembled monomolecular layer; Spin coating on self-assembled monolayers includes (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 and dimethylphenylethylthiodithiodide perovskite precursor solution, performing two-stage spin coating at different rotation speeds, adding chlorobenzene to the perovskite precursor solution before the end of spin coating, and annealing after spin coating to obtain a perovskite light absorbing layer; Spin coating a solution including a passivation material on the perovskite light absorbing layer, and annealing after spin coating to form a passivation layer; An electron transport material and a top electrode material are sequentially deposited on the passivation layer by vacuum evaporation to form an electron transport layer and a top electrode layer, respectively, to constitute a perovskite solar cell.
10. A photovoltaic device, characterized in that: A perovskite solar cell comprising any one of claims 1 to 8.